KONTRIBUSI PENGGUNAAN TENAGA KERJA DALAM KELUARGA TERHADAP PENDAPATAN USAHATANI PADI (Oriza Sativa, L) VARIETAS SIAM MUTIARA PADA LAHAN PASANG SURUT DI DESA BATIK KECAMATAN BAKUMPAI KABUPATEN BARITO KUALA PROVINSI KALIMANTAN SELATAN - Rohansyah (Fakultas Pertanian UVAYA Banjarmasin, 2020)
Purpose of this study was to determine the technical implementation of Siam Mutiara rice farming , costs, revenues, income and analyze the contribution of labor within the family in the family (TKDK) in the village of Batik. Determination farmer sample in this study was conducted using a technique purposivesampling and simple random sampling. Then, from a population of Siam Mutiara rice farmers samples were taken by using simple random sampling where each farmer has an equal opportunity to be taken as a sample, which is taken as many as 30% of the 90 farmers so that the farmers obtained 27 samples.The data analyzedin this study include primary data and secondary data. Primary data obtained from respondents in the field by conducting direct interviews with the assistance of the questionsheet. While secondary data obtained from relevant agencies and a review of materials in thelibrary.The data obtained were analyzed by tabulating the financial analysis regarding costs,revenues and earnings, as well as the Contributions of Labour in the Family. Based on theanalysis conclude that the amount of the contribution of labor in farming families an averageof 20.69% of the entire opinion of the Siam Mutiara rice farming in this area.